Total Productive Maintenance Strategy In A Semiconductor Manufacturer: A Case Study - K.C. Ng; Chong, Kuan Eng; G.G.G. Goh (2013)
The role of maintenance in manufacturing has become more crucial and important in today’s competitive environment. It is estimated that maintenance cost contributed approximately 10-30 percent of total operation cost. In order to stay competitive, manufacturing companies are forced to introduce production improvement programs to increase both quality and productivity. Total productive maintenance (TPM) is a well-known and very useful methodology which allows manufacturing firms to attain near ideal conditions with zero downtime, zero defects and zero accident. The objective of this paper is to study the effectiveness of TPM implementation in a multinational semiconductor manufacturer. In this study a bottleneck process from the production line was chosen and continuous improvements were implemented to improve equipment effectiveness. The results achieved are very encouraging in the reduction of equipment downtime, improvement in overall equipment effectiveness, employee motivation and reduction in number of accidence rate at the shop-floor.